Relationship between Inter-Functional Coordination On Performance Of Universities In Kenya - Chebet, J.; Muhanji, Stella; Njehia, Bernard; Bowen, Daisy (KABARAK UNIVERSITY, 2019)
Inter-functional coordination is one of the market orientation components which is based on the customer and competitor information entailing a business’s coordinated efforts involving not only marketing department, but all the organizations’ departments and resources in order to create superior value for customers. The main purpose of the study was to analyse the relationship between inter-functional coordination on performance of universities in Kenya. The philosophical foundation of this study was positivism. Descriptive and correlation designs design was adopted for the study. The target population for this study was 63 universities in Kenya. A total of 115 respondents who include 3 staff and 2 students were selected from a sample of 23 universities. Both stratified sampling and purposive sampling were used in selecting respondents from the population. A structured questionnaire, administered through drop and pick was used in collecting data. Descriptive and inferential statistics were used in analysing data through the multiple linear regression by using of Stata software, SAS System and Statistical Package for Social Sciences. The relationship between market orientation and university performance were analysed using correlation analysis. The analysed data was presented in frequency tables, pie charts, graphs and percentages. The results show that there was a significant positive relationship between inter-functional coordination and university performance at 1% level of significance respectively. This mean that the independent variable inter-functional coordination was significant in performance of universities. The study concludes that universities in Kenya were market oriented through inter-functional coordination. Implying that that inter-functional coordination is an important market orientation concept that needs to be adopted and implemented by universities in Kenya. This study recommends that universities in Kenya should make an effort and focus more on ensuring smooth flow of communication and sharing of information across all the university’s departments. The university management need to know that their institutions would perform well if they develop inter-functional coordination capabilities that will support competitive behaviour of innovativeness.
Full text
Keywords: Market Orientation, Inter-functional Coordination, Performance